2023
DOI: 10.1021/envhealth.3c00116
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: Dimensions of Environment and Health in Arctic Communities

Rainer Lohmann,
Bonita Beatty,
Jessica Graybill
et al.

Abstract: In the Arctic, environment and health are linked in myriad ways. A key emphasis has been on numerous long-lived contaminants in traditional foods, particularly marine mammals, and their well-documented impacts on human, animal and environmental health ("One health approach"). More recent concerns for Indigenous communities focus on the (side) effects of the switch to a modern, processed diet, which is accompanied by a loss of tradition and emerging health impacts. Furthermore, the availability of traditional f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…From the 56 reviewed papers, 53 in English and 3 in Russian were included in the Table . A total of 25 papers discuss the impacts of climate change on human health across various Arctic regions, addressing factors such as an increase in the mean annual or seasonal temperatures, alterations in precipitation patterns, sea level rise, permafrost degradation, and others. These changes pose heightened risks to overall human health in its different aspects (8) [45][46][47][48][49][50][51], including infectious disease, which represent a significant and frequent category regarding mortality and morbidity (13) [52][53][54][55][56][57][58][59][60][61][62][63][64], and mental health conditions (4) [63][64][65][66]. The remaining 31 papers focus on specific consequences of climate change, including extreme weather events like heat waves or cold spells, or cold climate implications in general (12) [67][68][69][70][71][72][73][74][75][76][77][78][79][80].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From the 56 reviewed papers, 53 in English and 3 in Russian were included in the Table . A total of 25 papers discuss the impacts of climate change on human health across various Arctic regions, addressing factors such as an increase in the mean annual or seasonal temperatures, alterations in precipitation patterns, sea level rise, permafrost degradation, and others. These changes pose heightened risks to overall human health in its different aspects (8) [45][46][47][48][49][50][51], including infectious disease, which represent a significant and frequent category regarding mortality and morbidity (13) [52][53][54][55][56][57][58][59][60][61][62][63][64], and mental health conditions (4) [63][64][65][66]. The remaining 31 papers focus on specific consequences of climate change, including extreme weather events like heat waves or cold spells, or cold climate implications in general (12) [67][68][69][70][71][72][73][74][75][76][77][78][79][80].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the complex and interconnected nature of climate change consequences, which can sometimes have cascading effects, it is challenging to separate them and their associated health outcomes. Hence, authors often address them within a single research agenda to provide a comprehensive understanding of the issues [44,46,49,50]. As an example, M. Brubaker et al [45] demonstrated the multifaceted impacts of climate change as heightening vulnerability to injury, disease, mental stress, and food and water insecurity [43].…”
Section: Climate Change and Multiple Risks For Human Healthmentioning
confidence: 99%
See 3 more Smart Citations